Circumventing Unintended Impacts of Waste N95 Facemask Generated during the COVID-19 Pandemic: A Conceptual Design Approach - Oseweuba Valentine Okoro; Adjoa Nkrumah Banson; Hongxia Zhang (ChemEngineering, 2020)
The global crisis arising from the current COVID-19 pandemic has resulted in a surge in the magnitude of global waste from used Personal Protective Equipment with special emphasis on waste N95 facemask. Creative approaches are therefore required to resolve the surging facemask waste disposal issue in an economical and environmentally friendly manner. In an attempt to resolve the evolving global waste challenge, the present study has assessed the economic and environmental performances of converting N95 facemasks to steam and electricity via a combined heat and power plant, to ethanol via a syngas fermentation process, and to an energy-dense gasoline-like oil product via a hydrothermal liquefaction process. These processes were assessed using “conceptual” process models developed using ASPEN plus as the process simulation tool. Economic and environment assessments were undertaken using net present values (NPVs) and the rate of potential environmental impacts (PEIs) respectively, as sufficient performance measures. Therefore, the present study was able to establish that the conversion of waste N95 facemask to syngas prior to a fermentation process for ethanol production constituted the least economical and least environmental friendly process with a negative NPV and the highest rate of PEI (1.59 PEI/h) value calculated. The NPV values calculated for N95 facemask waste conversion to steam and electricity and energy-dense oil processes were US$ 36.6 × 106 and US$ 53 × 106 respectively, suggesting the preference for the production of a valuable energy-dense oil product. Furthermore, it was observed that when the environmental performance of both processes was considered, rates of PEIs of 1.20 and 0.28 PEI/h were estimated for the energy-dense oil production process and the steam and electricity generation process, respectively. Therefore, the study was able to establish that the utilisation of waste N95 facemask for steam and electricity generation and for generating an energy-dense oil product are both promising approaches that could aid in the resolution of the waste issue if both environmental and economic performances constitute crucial considerations.